Quasi-phase-matching of high harmonic generation using counter-propagation pulses - O' Keeffe, K; Hooker, S (2013)
We investigate quasi-phase-matching over a range of harmonic orders using trains of up to 8 uniformly-spaced counter-propagating pulses. For trains of up to 4 pulses the measured enhancement of the harmonic signal scales with the number of pulses N as (N+1)2, as expected. However, for trains with N > 4, no further enhancement of the harmonic signal is observed. The effect is ascribed to changes in the coherence length with the generating medium. The pressure dependence of quasi-phase-matching is also investigated and it is found that additional peaks in the harmonic intensity are consistent with higher-order QPM processes. © Owned by the authors, published by EDP Sciences, 2013.